Assessment of Learning and Acquisition of Scientific Temper - PANCHAPAKESAN, N. (SCHOOL SCIENCE, 2006)
WE ARE at the end of the year ‘World Year of Physics’. It celebrates the centenary of Albert Einstein’s ‘Special Theory of Relativity’ given in 1905. It is said that this theory removes absolutism and brings in the idea of relativism. Every inertial observer has his own time and event simultaneities. No one observer is special in any way. Put another way, everyone is unique! Philosophers say that this (along with other events) has led to ethical relativism.